Compensation point phenomena in a graphene-like Ising nanoparticle decorated with spin-3/2 atoms. (March 2021) - Kaneyoshi, T.
Abstract: The possibility of a graphene-like Ising nanoparticle with high critical temperature or with a compensation point below its critical temperature is examined by decorating spin-3/2 atoms on the graphene-like Ising nanoparticle. The phase diagram and the temperature dependences of magnetization in the decorated nanoparticle are investigated by using the effective-field approximation with correlations. It is clarified how the paramagnetic graphene-like nanoparticle may change to a magnetic ordering nanoparticle by changing the physical parameters of decorated atom. Highlights: The graphene-like Ising nanoparticle decorated with spin-3/2 atom is discussed. The possibility of the decorated nanoparticle with high critical temperature is clarified. The possibility of a compensation point is studied. These are investigated by using the EFT.